Career and family - are they compatible?: Results of a survey of male and female gynaecologists in Germany - Hancke, Katharina; Toth, Bettina (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Nowadays, most gynaecologists are female and the compatibility of job-related career and family life is an upcoming issue. The working group “Gender and Career” of the German Society for Gynaecology and Obstetrics (DGGG) designed a survey to reflect the present situation with a focus on the compatibility of career and family. Material and Methods: A web-based 74-item survey was filled out by members of the DGGG. In total, there were 1037 replies, 75 % female (n = 775) and 25 % male (n = 261) gynaecologists. Results: 62% of the female and 80 % of the male respondents had already finished their doctoral theses and 2 % female and 13% male had finished their PhD. Mean number of children was 1.06 (SD 1.08) in female and 1.68 (SD 1.34) in male gynaecologists. The majority of females desired day care for their children, but only 5 to 13% of employers offer any day care. 88% of the female and 72% of the male physicians think that job-related career and family are not compatible. Conclusion: The majority of female gynaecologists wished to have professional child care, but most employers or other institutions do not offer this. This might be one of the reasons why career and family appear incompatible.